DIAGNOSTICS AS THE WAY OF FIRST YEAR STUDENTS’ LEARNING MATHEMATICS IN HIGHER SCHOOL - Chikina, Tatiana Evgenyevna (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2016)
Purpose. It is known that traditional system of knowledge control predominates in higher schools. This system allows only to focus on the results of how students have been able to master a discipline but not to find out reasons of making mistakes in disciplines including Ma- thematics. It means that operative diagnostics is not used properly. In order to solve the problem of first year students’ adaptation in learning professional aspect it is very important to shift the focus from control to diagnostics, to formation of both self-control and self-assessment. Thereby, it is necessary to work out the adequate system of diagnostic assignments, ways of operative diagnostics containing educator’s control, inter-control and self-control. Materials and methods. Both analysis and synthesis of scientific literature data concerning the research issue; surveillance, questionnaires, pedagogical diagnostics; generalization, systematization. Results. The carried out research has shown that in order to introduce well-timed correctives into learning process aimed at acceleration of students’ adaptation, it is necessary to use entering and current diagnostics, diagnostic assignments on both operational and reflexive-assessed stages of practical classes and in the process of academic counseling as well. The article emphasizes the principles of constructing diagnostic assignments used by us in the process of teaching Maths. The principles coincide substantially with both learning and adaptation purposes, and are constructed with provision for stages of mastering learning information and kinds of students’ learning-cognitive activities. Practical implications. The theses and conclusions given in the article should help to raise the efficiency of students’ learning and educational process during their adaptive period, and can be realized in the practice of higher schools.